2019
DOI: 10.18203/2320-1770.ijrcog20193808
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge about obstetric danger signs among pregnant women attending antenatal clinic in a tertiary care hospital of Delhi: a cross sectional study

Abstract: Background: According to UNICEF, globally 800 million women die due to preventable causes related to pregnancy and childbirth; 20% of which occur in India. It is therefore imperative to understand the level of knowledge about danger signs among pregnant women to augment timely redressal of preventive obstetric causes of mortality.Methods: A hospital based, cross sectional study was conducted at the ANC Clinic in Safdarjung Hospital, New Delhi from 2nd July to 27th July 2018. Convenient sampling was used to ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 8 publications
3
4
2
Order By: Relevance
“…This nding is similar to studies carried out by Morhason-Bella et al in Nigeria [27] , Hailu et al in Ethiopia [7] and Kabakyenga et al in Uganda [28] where the most commonly mention danger signs were per vagina bleeding, abdominal pain severe headache/blurred vision and fever. However, this nding is contrary to ndings by Kumar A et al in Delhi, India [26] were the commonly mentioned pregnancy danger sign was abdominal pain followed by per vaginal bleeding. The reason vaginal bleeding was commonly mentioned could possibly be because it is the most visible sign compared with other signs such as reduced foetal movement that need keen attention to notice.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This nding is similar to studies carried out by Morhason-Bella et al in Nigeria [27] , Hailu et al in Ethiopia [7] and Kabakyenga et al in Uganda [28] where the most commonly mention danger signs were per vagina bleeding, abdominal pain severe headache/blurred vision and fever. However, this nding is contrary to ndings by Kumar A et al in Delhi, India [26] were the commonly mentioned pregnancy danger sign was abdominal pain followed by per vaginal bleeding. The reason vaginal bleeding was commonly mentioned could possibly be because it is the most visible sign compared with other signs such as reduced foetal movement that need keen attention to notice.…”
Section: Discussioncontrasting
confidence: 99%
“…A possible explanation could be because, these studies were community based and participants were women who gave birth one to two years prior to the survey, secondly majority of participants in our study 268(68%) had attended at least high school, compared to other studies where most of the participants had only secondary school education. However, our nding was low compared to studies carried out in Rural Madagascar [25] and Delhi, India [26]. This difference in results can be attributed to, rstly the different criteria used for assessing knowledge (a woman was considered to have good knowledge if she spontaneously mentioned at least two/one danger sign respectively, whereas in our study good knowledge was considered when a participant spontaneously mentioned at least four danger signs.…”
Section: Discussioncontrasting
confidence: 82%
“…17,23 It was lower than some studies conducted in Ethiopia, 26,30,31 Uganda, 37 Madagascar, 28 and India. 38,39 But it was higher than some studies conducted in Ethiopia, 2,[32][33][34]40 Tanzania, 13 and Kenya. 10 The variation observed compared to other studies could be due to the differences in sample size, the operational definition used (most studies used two, some used three and others used four, and so on criteria to say knowledgeable about PDSs), and methodology in general.…”
Section: Discussionmentioning
confidence: 78%
“…4 Globally 800 million women die due to preventable causes related to pregnancy and childbirth; 20% of which occur in India. 5 It was reported that in India around 44,000 women die due to pregnancy and childbirth related complications. The high number of maternal deaths in some areas of the world reflects inequities in access to health services, rampant illiteracy, ignorance and gender inequality.…”
Section: Introductionmentioning
confidence: 99%
“…The risk of maternal mortality is highest for adolescent girls under 15 years of age. 5 The maternal mortality ratio (MMR) for Nepal is 239 deaths per 100,000 live births in 2016. Nepal has committed to doing its part to achieve Sustainable Development Goal (SDG) target 3.1 of reducing the global MMR to less than 70 maternal deaths per 100,000 live births by 2030.…”
Section: Introductionmentioning
confidence: 99%